Taka-dollar exchange rate dynamics in relation to federal interest rates and the Bangladesh-USA trade balance: a time series analysis - Zaman, Foara (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Applied Economics, 2024.